Validity and reliability of 10 Hz GPS sensor for measuring distance and maximal speed in soccer: Possible differences of unit positioning - Akyildiz, Z.; Alvurdu, S.; Ceylan, H. I.; Clemente, F. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
In contemporary research literature, inconsistencies regarding the validity and reliability of different brands of global positioning systems (GPSs) have been reported regarding the positioning of GPS units on athletes. For this reason, the present work investigates the validity and reliability of the measurements of GPS units placed at different locations. Thirty-two amateur soccer players (age: 21.18 ± 3.16 years; height: 175 ± 8.03 cm; body mass: 74.21 ± 4.85 kg) voluntarily participated in the current study. Participants were asked to complete a team sport simulation cycle (TSSC). During the tests, two GPS units were placed between the shoulder blades and on the chest of each athlete. Data from Polar Team Pro GPS units at both locations on the body, previously measured test area distance, and a radar gun (the gold standard) were compared to determine validity. The reliability of GPS units in measuring maximum speed is moderate (CV = 9.77-9.08, ICC = 0.23). The reliability of GPS units in measuring total distance is good (CV = 4.43-9.39, ICC = 0.15). The reliability of GPS units in measuring distance covered is poor (CV = 17.51-35.37). The measurements of total distance covered, and maximum speed recorded by the chest and back GPS units are not valid (Max speed = GPS chest-radar gun; R2 = 0.075, GPS back-radar gun; R2 = 0.106, total distance = GPS chest-1200 m; R2 = 0.003, GPS back-1200 m; R2 = 0.097). Consequently, it can be said that 10-Hz Polar GPS sensors have good reliability for measuring total distance when placed on the chest and moderate reliability for measuring peak speed when placed on the chest and back; however, they have poor reliability at both positions for evaluating distances at different running speeds.